Produksi Menurut Muhammad Abdul Mannan Dan Relevansinya Terhadap Sustainable Development Goals (SDGS) - Rahmat Fitriansyah; Nurul Huda (Jurnal Ilmiah Ekonomi Islam, 2023)
Islam controls all aspects of human economic life, including production, distribution, and consumption—activities that are crucial for generating economic growth. According to an article by Abdul Mannan, this production paradigm establishes the idea that morality and profit are both important factors in economic welfare. This study is driven by moral responsibility disparities that are at odds with the idea of production and a need to examine how thinking relates to the SDGs agenda. In-depth analysis of this relevance is done using the characters' thinking. This study employs a qualitative methodology, a library research approach, and content analysis as the research tool. This investigation clarifies Mannan's theory of production. The findings of this study demonstrate that Mannan's ideas about Islamic production are highly pertinent to the SDGs, which can also promote moral responsibility in every aspect of production.